2011
DOI: 10.1139/w11-003
|View full text |Cite
|
Sign up to set email alerts
|

Comparing sediment bacterial communities in the macrophyte-dominated and algae-dominated areas of eutrophic Lake Taihu, China

Abstract: Bacterial community structure and the effects of several environmental factors on bacterial community distribution were investigated in the sediment of the macrophyte-dominated and algae-dominated areas in a large, shallow, eutrophic freshwater lake (Lake Taihu, China). Surface sediment samples were collected at 6 sampling sites (3 sites from each of the 2 areas) on 15 February and 15 August 2009. Based on cluster analysis of the DGGE banding patterns, there were significant seasonal variations in the structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
25
4

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 33 publications
7
25
4
Order By: Relevance
“…These changes might be related to the responds of these bacteria to the nutrient conditions of the sediments during different bloom stages, since they have been described as the degraders of organic nutrient in marine sediment (Sinkko et al 2013). Our results demonstrated that the Alphaproteobacteria were more abundant during the algal bloom, which is similar to the findings elsewhere (Eiler et al 2006;Shao et al 2011;Ye et al 2009). The changes of anaerobic phototrophic bacteria Chlorobi and Chloroflexi might be related to the turbidity of the water body, since the bloom can block the transmission of light to the surface of sediments.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…These changes might be related to the responds of these bacteria to the nutrient conditions of the sediments during different bloom stages, since they have been described as the degraders of organic nutrient in marine sediment (Sinkko et al 2013). Our results demonstrated that the Alphaproteobacteria were more abundant during the algal bloom, which is similar to the findings elsewhere (Eiler et al 2006;Shao et al 2011;Ye et al 2009). The changes of anaerobic phototrophic bacteria Chlorobi and Chloroflexi might be related to the turbidity of the water body, since the bloom can block the transmission of light to the surface of sediments.…”
Section: Discussionsupporting
confidence: 88%
“…However, the Betaproteobacteria as the most dominant bacterial group in all the sediments sampled in the four periods from different sites of Taihu was a result different from the observation in a previous study (Shao et al 2011), in which Shao et al (2011 reported that Deltaproteobacteria was the most dominant classes in macrophyte-dominated areas and Betaproteobacteria was the most dominant classes in algaedominated areas of the Lake Taihu. This difference might be due to the fact that DGGE and sequencing methods were used in Shao et al (2011), which have less resolution than the pyrosequencing technique. In addition, Shao et al (2011) reported that Epsilonproteobacteria (21.1 %) were the second dominant group of sediment bacteria in the macrophyte-dominated state, but not in the algaedominated state.…”
Section: Discussioncontrasting
confidence: 80%
See 3 more Smart Citations